2011
DOI: 10.15628/holos.2011.638
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Sensorial De Goiabas Passas Obtida Por Técnicas Combinadas De Desidratação Osmótica E Secagem

Abstract: A goiaba (Psiduim guajava L.) é utilizada não apenas para o consumo “in natura” como também para atender a uma demanda substancial para conservas industriais possibilitando, pela sua desidratação, um novo insumo nas indústrias alimentícias. Com vistas a atender a este mercado, o objetivo deste trabalho foi realizar a análise sensorial da goiaba passa da variedade Paluma obtida utilizando-se técnicas combinadas de desidratação osmótica e secagem convencional. Utilizaram-se goiabas nos estádios de maturação verd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…PB3 had the highest CC between the DB and NDB participants. Pessoa et al (2011) verified that the highest CCs were found for the highest ratings, confirming that the best sample has the highest CC. Accordingly, PB3 was the most accepted formulation by the participants, as it had both the highest frequency of ratings of 9 and the highest CC.…”
Section: Acceptabilitysupporting
confidence: 55%
“…PB3 had the highest CC between the DB and NDB participants. Pessoa et al (2011) verified that the highest CCs were found for the highest ratings, confirming that the best sample has the highest CC. Accordingly, PB3 was the most accepted formulation by the participants, as it had both the highest frequency of ratings of 9 and the highest CC.…”
Section: Acceptabilitysupporting
confidence: 55%
“…no terceiro e sétimo dia após a aplicação dos tratamentos (Instituto Adolfo Lutz, 2008). As amostras de goiaba foram cortadas em fatias e depositadas em copos descartáveis codificados com algarismos de três dígitos e aleatorizadas (Pessoa et al, 2011). As amostras foram apresentadas para 20 julgadores não treinados com idade entre 18 e 34 anos para analisar os atributos: aparência, aroma, cor, sabor e firmeza da polpa de seis formulações de biofilme a base de fécula de mandioca e extratos vegetais de cravo da índia e melão-de-são-caetano mais a testemunha sem…”
Section: Methodsunclassified
“…Osmotic dehydration as drying pre-processing has been widely used for reducing up to 50% of the water content contained in the food, giving the final product a better quality regarding appearance, flavor, aroma and texture (Goetten et al, 2016). According to Cardoso et al (2018), the combination of drying techniques creates possibilities for new products with characteristics of the fresh product, conserving and improving the stability of the product during storage (Pessoa et al, 2011).…”
Section: Introductionmentioning
confidence: 99%